Fitness vs Fatness as Determinants of Survival in Noninstitutionalized Older Adults: The EXERNET Multicenter Study. Issue 5 (21st June 2021) - Navarrete-Villanueva, David; Gómez-Cabello, Alba; Gómez-Bruton, Alejandro; Gesteiro, Eva; Rodríguez-Gómez, Irene; Pérez-Gómez, Jorge; Villa-Vicente, José Gerardo; Espino-Toron, Luis; Gusi, Narcís; González-Gross, Marcela; Ara, Ignacio; Vicente-Rodríguez, Germán; et al.
Abstract: Background: Physical fitness and body composition are important health indicators; nevertheless, their combined pattern interrelationships and their association with mortality are poorly investigated. Methods: This longitudinal study is part of the Spanish EXERNET-Elder project. Person-months of follow-up were calculated from the interview date, performed between June 2008 and November 2009, until the date of death or censoring on March 2018 (whichever came first). In order to be included, participants had to fulfill the following criteria: (a) be older than 65 years, (b) live independently at home, (c) not suffer dementia and/or cancer, and (d) have a body mass index above 18.5. Body fat and weight were assessed by a bioelectrical impedance analyzer. Fitness was measured with the Senior Fitness and the one-leg static balance tests. The Spanish Death Index was consulted for the death's identification. Cluster analysis was performed to identify Fat–Fit patterns and traditional cut-points and percentiles to create the Fat–Fit groups. Cox proportional hazards regression models were used to calculate the hazard ratios (HRs) of death in clustered Fat–Fit patterns and in traditional Fat–Fit groups. Results: A total of 2299 older adults (76.8% of women) were included with a baseline mean age of 71.9 ± 5.2 years. A total of 196 deaths (8.7% of the sample) were identified during the 8 years of follow-up. Four clustered Fat–Fit patterns (Low fat–Fit, Medium fat–Fit, High fat–Unfit, and Low fat–Unfit) and 9 traditional Fat–Fit groups emerged. Using the Low fat–Fit pattern as the reference, significantly increased mortality was noted in High fat–Unfit (HR: 1.68, CI: 1.06–2.66) and Low fat–Unfit (HR: 2.01, CI: 1.28–3.16) groups. All the traditional Fit groups showed lower mortality risk when compared to the reference group (obese–unfit group). Conclusion: Physical fitness is a determinant factor in terms of survival in community-dwelling older adults, independently of adiposity levels.